Efficient weed management through appropriate herbicides in groundnut - Singh, R K; Tripathi, U K; Rawat, Anay (Indian Farming, 2022)
It can be stated that the imazethapyr along with quizalofop-ethyl can effectively control different categories of weeds in groundnut field. Higher economic yields may be achieved in groundnut crop without any phytotoxic effect under the treatment (Imazethapyr 10% SL @ 100 g a.i./ ha + Quizalofop-ethyl 5% EC @ 37.5 g a.i/ha at 20 DAS), where crops matured earlier than the control plots.